2018
DOI: 10.1038/s41579-018-0140-y
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Host and viral determinants of influenza A virus species specificity

Abstract: In the section on initial attachment and in Figure 1 it was erroneously indicated that enterococcal surface protein (Esp) binds collagen and fibrinogen. The text and figure were changed to remove this binding interaction both online and in the pdf. The authors apologize for any confusion caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…IVPI tests confirmed that the XL virus had low pathogenicity in chickens. Q/G225D, Q226L, S227N, and G228S mutations in HA proteins have been reported to increase SA-α2,6-Gal binding affinity ( 39 , 40 ). Previous studies showed that H7N9 AIVs with low pathogenicity with residues 186V and 226L on the HA protein bound to SA-α2,6-Gal receptors with high affinity ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…IVPI tests confirmed that the XL virus had low pathogenicity in chickens. Q/G225D, Q226L, S227N, and G228S mutations in HA proteins have been reported to increase SA-α2,6-Gal binding affinity ( 39 , 40 ). Previous studies showed that H7N9 AIVs with low pathogenicity with residues 186V and 226L on the HA protein bound to SA-α2,6-Gal receptors with high affinity ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the efficient infection of human populations from avian reservoirs, AIVs must overcome the species barriers through adaptive evolution [ 33 ]. Multiple adaptive mutations in viral hemagglutinin (HA) and polymerase subunits are recognized to be necessary for the efficient infection of AIVs in their new host, even in humans [ 34 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HA is a major factor for host specificity (35, 36) and is a prime target for evolution as a human seasonal virus adapts to the swine host. Specific amino acid substitutions at or near the RBS have been shown to alter receptor binding or antigenicity of influenza viruses (5, 37, 38), which likely affects host specificity.…”
Section: Discussionmentioning
confidence: 99%